Understanding LTE and its Performance - Ali-Yahiya, Tara.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Mobile communications technology is developing so rapidly that it seems a new breakthrough makes the headlines each week. Aimed at a wide audience, this book guides the reader through the complexities of Long Term Evolution (LTE) networks. Advanced LTEs are set to play a central role in the rapid take-up of fourth-generation mobile services able to deliver download speeds of hundreds of megabits a second. Beginning with the basic principles of LTE networks, the text builds to in-depth coverage of more complex topics, including a detailed assessment of LTE release 8, which forms the baseline specification of LTE 3GPP, the set of standards laid down by the Third Generation Partnership Project. The wealth of subjects discussed includes the network architecture and programming required to ensure 4G LTE compatibility with 2- and 3G systems such as WiMAX, and the ways in which cell interference can be minimized. With faster, multilayered 4G networks set to spread to the remotest areas, this vital resource will be required reading for anyone needing to grasp the fundamentals of mobile communications.
Introduction to Mobile Broadband Wireless -- Network Architecture Protocols -- LTE Radio Layer Design -- LTE Physical Layer -- Quality of Service -- Interworking Design for LTE Convergence -- Mobility -- LTE and Femtocell -- Downlink Radio Resource Allocation Strategies in LTE Networks -- Performance Study of Opportunistic Scheduling in LTE Networks -- Cross-Layer Multiservice Scheduling for LTE Networks -- Fractional Frequency Reuse in LTE Networks -- Performance Study of Mobile WiMAX and LTE Interworking -- LTE Femtocell Integration with Wireless Sensor/Actuator Networks and RFID Technologies -- Appendix: LTE Operators -- Index.
Keywords: Engineering; Computer Communication Networks; Telecommunication; Engineering; Communications Engineering, Networks; Computer Communication Networks; Signal, Image and Speech Processing